Faktor yang Mempengaruhi Konsistensi Perencanaan dan Penganggaran pada Pemerintah Kota Kupang dengan Komitmen Organisasi sebagai Variabel Mediasi - Koli, Feby Rosaline; Perseveranda, M. E.; Sonbay, Yolinda Yanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The objective of this study is to comprehend the Kupang City Government's overall budget participation, planning and budgeting rules, opportunistic behaviour, consistency of planning and budgeting, and organisational commitment. Additionally, the study intends to assess the impact of budget participation, planning and budgeting regulations, opportunistic behaviour, and organisational commitment on organisational commitment. Finally, it seeks to ascertain whether these factors significantly affect the consistency of planning and budgeting in the Kupang City Government. This study also seeks to ascertain if organisational commitment acts as a mediating factor in the relationship between the consistency of planning and budgeting and budget participation, planning and budgeting laws, and opportunistic behaviour.The Kupang City Government's State Civil Apparatus (ASN) constitutes the study's population. Specifically, 114 ASN are actively involved in planning, budgeting, and reporting activities across all regional apparatuses. The SmartPLS programme is used for data analysis.The variables of budget participation, planning and budgeting regulations, opportunistic behaviour, and consistency of planning and budgeting in the Kupang City Government fall into the good category, according to the results of the descriptive statistical analysis, while organisational commitment is in the quite good range. Path analysis shows that organisational commitment, opportunistic behaviour, and budget involvement all significantly affect how consistently planning and budgeting occur. Regulating planning and budgeting, however, does not much affect how consistently planning and budgeting are done.While opportunistic behaviour does not significantly affect organisational commitment, budget participation and planning and budgeting requirements are proven to have a considerable impact. Additionally, the impact of budget participation and planning and budgeting regulations on the consistency of planning and budgeting is significantly mitigated by organisational commitment; however, the impact of opportunistic behaviour on the same is not significantly mitigated.